Brucella vertebral osteomyelitis misidentified as an Ochrobactrum anthropi infection. (2018) - Trêpa, João; Mendes, Patricia; Gonçalves, Raquel; Chaves, Catarina; Brás, Ana Maria; Mesa, Andrea; Ramos, Isabel; Sá, Rosa; da Cunha, José Gabriel Saraiva
Abstract: Ochrobactrum anthropi is a Gram-negative bacillus widely distributed in nature. It is a low virulence and low pathogenic microorganism and human infection by this agent is considered rare. This microorganism can cause bacteremia and in some cases can lead to osteomyelitis and endocarditis. Included in Brucellaceae family, this bacterium is phenotypically and genetically closely related to the Brucella genus and may be misidentified by rapid identification systems. The authors describe a patient admitted to the Infectious Diseases Department with vertebral osteomyelitis initially identified as Ochrobactrum anthropi . Despite appropriate antimicrobial therapy, the blood cultures remained positive and there were no signs of clinical improvement. This raised suspicion of a possible misidentification. It was decided to initiate antimicrobial therapy to include the Brucella genus, with slow but progressive clinical improvement. Samples were sent to Instituto Nacional de Saúde Doutor Ricardo Jorge (INSA) for genotyping, confirming the initial suspicion of misidentification and identifying Brucella melitensis as the causal agent. Timely diagnosis of brucellosis is essential for the correct management and prevention of its consequences for the patient and for safe handling of the laboratory samples, preventing laboratory-acquired infection